2017
DOI: 10.1111/anae.13964
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐operative protective mechanical ventilation in lung transplantation: a randomised, controlled trial

Abstract: Primary graft dysfunction occurs in up to 25% of patients after lung transplantation. Contributing factors include ventilator-induced lung injury, cardiopulmonary bypass, ischaemia-reperfusion injury and excessive fluid administration. We evaluated the feasibility, safety and efficacy of an open-lung protective ventilation strategy aimed at reducing ventilator-induced lung injury. We enrolled adult patients scheduled to undergo bilateral sequential lung transplantation, and randomly assigned them to either a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…For example, studies in multiple settings have been unable to show that temporary gains in either lung mechanics or oxygenation extend to the postoperative environment, even when the recruitment maneuver is performed shortly before extubation 7079808182. However, the benefits of recruitment maneuvers may be enhanced or prolonged by the performance of repeated maneuvers 83.…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%
“…For example, studies in multiple settings have been unable to show that temporary gains in either lung mechanics or oxygenation extend to the postoperative environment, even when the recruitment maneuver is performed shortly before extubation 7079808182. However, the benefits of recruitment maneuvers may be enhanced or prolonged by the performance of repeated maneuvers 83.…”
Section: Evidence Based Strategies For Perioperative Lung Protective mentioning
confidence: 99%
“…Verbeek et al randomly assigned patients undergoing double lung transplantation to a control group that received volume-controlled ventilation with 5 cmH 2 O of PEEP and low tidal volumes (6 mL/kg for two lung ventilation and 4 mL/kg for one lung ventilation) or an alveolar recruitment group who were ventilated using pressure controlled ventilation at 16 cmH 2 O with 10 cmH 2 O of PEEP and a stepwise PEEP-based alveolar recruitment algorithm, with the final outcome being the arterial oxygen/inspired oxygen ratio 24 hours after the first lung was reperfused. 18 Although the primary outcome was the same in both groups, the patients who underwent the alveolar recruitment algorithm demonstrated an increased arterial oxygen/inspired oxygen ratio at the end of the surgery and a shorter time to tracheal extubation. 18 The purpose of the survey was to discover the international anesthetic lung transplantation practices to determine the similarities and differences in order to consider the development of guidelines in the management of these patients.…”
mentioning
confidence: 87%
“…18 Although the primary outcome was the same in both groups, the patients who underwent the alveolar recruitment algorithm demonstrated an increased arterial oxygen/inspired oxygen ratio at the end of the surgery and a shorter time to tracheal extubation. 18 The purpose of the survey was to discover the international anesthetic lung transplantation practices to determine the similarities and differences in order to consider the development of guidelines in the management of these patients. It is difficult to standardize the anesthetic management because of the heterogeneity of the disease processes that predispose patients to require lung transplantation; the heterogeneity of the surgical techniques, including triggers for the use of mechanical assist devices; and the heterogeneity of the medical management, including postoperative ventilation.…”
mentioning
confidence: 87%
“…In a recent descriptive, multicenter study in which 690 patients were enrolled, iPROVE network investigators have demonstrated that open lung approach with individualized PEEP can result in less PPCs when compared with available findings [56••]. Verbeek et al conducted a RCT trial using the open lung approach (stepwise recruitment, 10 cm H2O PEEP and 4-5 ml/kg TV during OLV) in 748 patients undergoing lung transplantation surgery [57]. They compared this approach with a conventional lung-protective strategy (5 cm H 2 O PEEP, 4 ml/kg TV without ARM) and found OLA to be related with reduced duration of mechanical ventilation.…”
Section: Combinations Of Low Tv Peep and Armmentioning
confidence: 99%